Assessment of a Point-Cloud Volume-of-Fluid method with sharp interface advection. (15th November 2022) - Castello Branco, Rodrigo L.F.; Kassar, Bruno B.M.; Carneiro, João N.E.; Nieckele, Angela O.
Abstract: Multiphase flows are ubiquitous in nature and industry. In order to fully describe multiphase systems, simulation approaches must be able to handle the interfaces separating the different phases properly. The Volume of Fluid (VOF) approach is widely used by researchers and engineers due to its intrinsic ability to conserve volume and handle large interface topology changes. A common problem that occurs in VOF Methods relates to the calculation of interfacial tension forces in the momentum equations while resolving a sharp interface. Common methods based on the gradients of the volume fraction field may lack accuracy due to the curvature and normal vector estimates through an abrupt transition. To address these points, the present work introduces a new proposal, where the VOF method based on a cloud of points for interface curvatures computation (PC-VOF) is extended by the coupling with the sharp-interface advection algorithm isoAdvector, implemented in the open source suite OpenFOAM®. The coupled method performs better than the ones implemented in the original solvers in a number of benchmark cases from the literature. It is shown to significantly reduce the spurious currents and also presents more stable and accurate results, especially for irregular triangular meshes. Highlights: A VOF method with CSF and Point Cloud (PC-VOF) surface tension models is assessed. PC-VOF is coupled with isoAdvector and MULES advection methods. PC-VOF/isoAdvector: smaller spurious currents, better mesh convergence, improved stability. PC-VOF/isoAdvector improved performance against analytical and benchmark data, particularly for irregular mesh.